ГРАЖДАНСКО-ПРАВОВАЯ ОТВЕТСТВЕННОСТЬ ГОСУДАРСТВА ЗА УЩЕРБ, ПРИЧИНЕННЫЙ ФИЗИЧЕСКИМ И ЮРИДИЧЕСКИМ ЛИЦАМ - Сосна, Александр (SUPREMANCE OF LAW, 2018)
The article highlights the normative acts establishing the civil liability of the state for damage caused by illegal actions (inactions) of state bodies and officials of these bodies. In the protection of the rights and freedoms of citizens, the responsibility of the state for damage caused to individuals and legal entities plays an important role. Without this, citizens’ rights cannot be effectively protected. Special attention is drawn to legal norms that create conditions conducive to the impunity of violations of the rights of individuals and legal entities by officials of state bodies. This article was prepared by the Institute for Democracy (Moldova). This article is funded by the European Union within the framework of the confidence-building measures programme- CBM IV The opinions expressed in the article do not necessarily reflect the views of the European Union.